1996
DOI: 10.1002/j.1460-2075.1996.tb01085.x
|View full text |Cite
|
Sign up to set email alerts
|

A microsomal ATP-binding protein involved in efficient protein transport into the mammalian endoplasmic reticulum.

Abstract: Protein transport into the mammalian endoplasmic reticulum depends on nucleoside triphosphates. Photoaffinity labelling of microsomes with azido‐ATP prevents protein transport at the level of association of precursor proteins with the components of the transport machinery, Sec61alpha and TRAM proteins. The same phenotype of inactivation was observed after depleting a microsomal detergent extract of ATP‐binding proteins by passage through ATP‐agarose and subsequent reconstitution of the pass‐through into proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 111 publications
3
99
1
Order By: Relevance
“…This may be because ORP150 is more efficient in binding peptides than is Hsp70. The ability of ORP150 to bind polypeptides better than other Hsp70 family members is largely due to its enlarged C-terminal helical domain (41,42). Moreover, it may help that peptide binding to ORP150 is independent of ATP, which is in contrast with ATP-dependent substrate binding of other Hsp70 family members (42).…”
Section: Discussionmentioning
confidence: 99%
“…This may be because ORP150 is more efficient in binding peptides than is Hsp70. The ability of ORP150 to bind polypeptides better than other Hsp70 family members is largely due to its enlarged C-terminal helical domain (41,42). Moreover, it may help that peptide binding to ORP150 is independent of ATP, which is in contrast with ATP-dependent substrate binding of other Hsp70 family members (42).…”
Section: Discussionmentioning
confidence: 99%
“…Less is understood at the molecular level of grp170 structure and function; however, cellular studies have shown that it binds to Ig chain in the ER, may be the ATPase responsible for protein import into the ER, and actively binds peptides from TAP (i.e., the transporter associated with Ag processing; Refs. 11,19,20,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The system is based on SP6-or T7-polymerase, reticulocyte lysate, and on either [ 35 S]methionine or [ 35 S]cysteine (Amersham) and was programmed with circular DNA. Rough microsomes from dog pancreas (11) were added at 7.5 equivalents (12) per 50 l translation mixture. After incubation for 45 min at 30°C the microsomes were sedimented for 5 min at 75,000 ϫ g and treated with 170 g͞ml proteinase K for 45 min at 0°C.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro translation products were chilled on ice and aliquots were boiled immediately with electrophoresis sample buffer. SDS͞ PAGE and fluorography were as described (11). High-Tris gels containing 17.5% acrylamide͞0.23% bis-acrylamide or (Fig.…”
Section: Methodsmentioning
confidence: 99%